Trust And Access in Telemedicine - A Review - Mabina, Alton (Journal of Health Informatics in Africa, 2026)
Background and Purpose: Telemedicine has the potential to revolutionise healthcare delivery, especially in digitally marginalised populations; however, persistent challenges in access and trust limit its widespread adoption. Despite technological advancements, there remains a significant gap in understanding how these factors jointly influence telemedicine uptake in low- and middle-income contexts.Methods: This study employed a systematic literature review guided by the PRISMA framework, analysing 32 peer-reviewed studies published between 2018 and 2025 that address access and trust in telemedicine.Results: Telemedicine interventions yielded notable access gains in underserved settings, with rural reach improving by 40–75% across multiple studies. Trust outcomes, however, were less consistent, with confidence levels ranging from 44–71% and often constrained by privacy concerns, provider scepticism, and technological reliabilityConclusions: This research contributes a comprehensive synthesis of empirical evidence highlighting the critical interplay between access and trust, providing actionable insights for designing user-centred, secure telemedicine systems. By addressing this dual gap, the study offers a foundation for future technological innovation and policy development aimed at equitable healthcare delivery in underserved populations.